Tinjauan Yuridis Suara Sebagai Merek dalam Undang-Undang Nomor 20 Tahun 2016 tentang Merek dan Indikasi Geografis - Kristina Sanca Ngunas; Made Gede Subha Karma Resen (Pemuliaan Keadilan, 2024)
Voice is one of the signs in a brand. Voice comes in in non-traditional brands. Sound marks are listed in Law Number 20 of 2016 concerning Marks and Geographical Indications. In the arrangements, there is still confusion regarding this matter, so that very few votes are registered in its implementation. A small number of vote registrations really creates problems of confusion in registration. This research uses normative research through a statutory and regulatory approach and a comparative approach. The results obtained from the research are that there are obstacles in registering sound as a brand so that sound brands are refused registration. This problem concerns the bad faith carried out by the registrant. Comparison of the regulation of sound as a brand in Australia and Indonesia has similarities and differences in registration. Australia has regulated sounds that cannot be registered and regulates the duration of sounds that will be branded. while Indonesia has not yet regulated this.